Creating a Regional Security Community in Southern Latin America: The Institutionalisation of the Regional Defence and Security Policies - Daniel Flemes (German Institute of Global and Area Studies (GIGA), 2005)
Interdependence, collective identities and common institutions are the preconditions for the evolution of a pluralistic security community. While the interaction of the states of Southern Latin America already meets the first two criteria, this article focuses on the third one, particularly the common institutions of the regional defence and security sector. The bilaterally organised defence cooperation has been attested democratic deficiencies because military actors are over-proportionally represented in these committees. Military nationalism and an exaggerated notion of national sovereignty in the military academies of the region can be regarded as cooperation hampering qualifiers. Non-military threats (organised crime, transnational terrorism) have centripetal effects on the subregional cooperation, which is structured multilaterally and shows a relatively high degree of institutionalisation.
Keywords: 300; security community; regional cooperation; defence and security policies; Latin America; Mercosur; Argentina; Brazil; Chile